Billie's secret - John, Laurie; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1996)
Billie Winkle is breaking Steven Wakefield's heart. By competing for a scholarship to study in Spain, she has shattered Steven's plans for their perfect future.
"The world of Sweet Valley"--P. 4 of cover.
"YA novel"--Spine.
Keywords: College students -- Fiction; College students -- Scholarships, fellowships, etc. -- Fiction; Scholarships -- Fiction; College stories; Love stories